Pengungkapan Diri Pasca Patah Hati Orang Dewasa Awal pada Aplikasi Tinder - Rizqi Ramadhani Hartawan; Siti Nursanti; Tri Widya Budhiharti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Self-disclosure is an essential aspect of interpersonal communication, especially for individuals who have recently experienced heartbreak. This study aims to understand how early adults disclose themselves after experiencing heartbreak, particularly through the online dating application, Tinder. The research method used is qualitative with a descriptive approach, involving in-depth interviews with five informants aged 20-30 who had experienced heartbreak before using Tinder. The results show that heartbreak encourages individuals to be more cautious in disclosing themselves. The self-disclosure process on Tinder occurs gradually, starting from general information to more profound levels, depending on the level of comfort and trust established. The motivations for using Tinder vary, ranging from the need to overcome loneliness to the desire to find conversation partners and new relationships. Negative emotional experiences make users more selective in choosing conversation topics and maintaining boundaries when disclosing personal information. These findings align with Altman and Taylor's Social Penetration Theory, which describes self-disclosure as a process that moves from shallow aspects to deeper ones as the level of trust between individuals increases. This study contributes to understanding the dynamics of self-disclosure in early adults after heartbreak, especially in the context of social media and online dating applications. The conclusion of this research emphasizes that emotional experiences affect how individuals open up and highlight the importance of trust in that process.